West African Economic and Monetary Union (WAEMU) : Staff Report on Common Policies for Member Countries-Press Release; Staff Report; and Statement by the Executive Director for the WAEMU. (IMF Staff Country Reports; Country Report, 2019)
This regional consultation IMF staff report for West African Economic and Monetary Union (WAEMU) highlights that growth remained strong in 2018, the fiscal deficit narrowed by 1/2 percentage point of GDP, external reserves increased, and important banking reforms were put in place, including the introduction of Basel II/III standards. The medium-term outlook remains positive despite somewhat less favorable global conditions, but critically hinges on planned fiscal consolidation and structural reforms to improve competitiveness and allow the private sector to become the main engine of growth. Other risks relate to terms-of-trade and weather shocks, and a difficult security situation in some countries. The report also discusses that collectively adhering to fiscal consolidation commitments, with a greater focus on domestic revenue mobilization and more effective control of below-the-line operations, is essential to lower risks of public debt distress, support international reserves, and preserve external viability. Structural policies aimed at improving competitiveness and growth inclusiveness are critical to reducing vulnerabilities to external shocks, building external buffers, stimulating private-sector-led growth, and making the growth momentum sustainable.